If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying w + -11 = 3 Reorder the terms: -11 + w = 3 Solving -11 + w = 3 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + w = 3 + 11 Combine like terms: -11 + 11 = 0 0 + w = 3 + 11 w = 3 + 11 Combine like terms: 3 + 11 = 14 w = 14 Simplifying w = 14
| 2(x)-8=x-7 | | 5v+25= | | 5(15x+5)=415 | | cos(x)=11x | | 7x^2+5x+h=0 | | ln(x+35)-ln(x-1)=ln(x-5) | | 6s^2+5s=0 | | 2+10(4x+5)= | | 3(x^2-14x)=-14 | | 6(-3x+4)=-120 | | .2x+.3y=.23(100) | | 5s^2-5s-7=0 | | -2s-7=5 | | 8s^2-6s-8=0 | | 48=x(16-x) | | 5w-7w+6+8w= | | 2s^2-3s+8=0 | | 4s+4=-28 | | 2s^2-6s+2=0 | | 6s^2-7s+1=0 | | Log^3(3-5x)=2 | | log(x-1)-log(x+2)=1 | | u^2-14u=43 | | ht=-5t^2+15t+2 | | u^2-26u-35=0 | | ab-b+c+17+6ab-34= | | -21p-15-4+40p=27-18p | | 4x^2+12x-15=5 | | u^2+4u-23=0 | | x^2+xy=24 | | 6.84*x=3 | | f(x)=x^3-4x+4 |